Changes in taste resulting from conventional chemotherapy (Research, Society and Development, 2021)
Cancer is linked to the disordered increase of cells, has the ability to invade neighboring tissues in the place of origin and/or install itself in distant organs via the bloodstream. Antineoplastic treatment can generate side effects in the oral mucosa, being evident through the appearance of oral mucositis. We can also observe changes in taste, such as: hypogeusia, dysgeusia, ageusia and hypergeusia. The present work aims to review the literature on taste alterations caused by 5-fluorouracil (5-FU), leucovorine, oxaliplatin, gemcitabine, capecitabine, cisplatin, cyclophosphamide, doxorubicin, irinotecan and methotrexate, being conventional antineoplastic drugs. This study was carried out by collecting data from 2009 to 2021, from scientific literature in the PubMed, Lilacs, Cochrane and Scielo databases in English and Spanish, using the key words Antineoplastics; Distorted taste; Dysgeusia; Stomatitis; Oral cavity; together with the Boolean operators “and” and “or”, in order to combine the aforementioned descriptors. Given the above, conventional chemotherapy drugs affect taste cells and biochemical processes related to their cell renewal, generating changes in taste such as hypogeusia, dysgeusia, ageusia and hypergeusia.